Intervenciones de enfermería en la promoción de la salud sexual y reproductiva. - Mita Pilamunga, Anai Liceth (2024)
Nursing interventions aimed at promoting sexual and reproductive health in adolescents are of utmost importance in public health. During adolescence, they face various fluctuations in their physical, psychological, and social state, which may lead them to be susceptible to adopting risky behaviors due to their immaturity and lack of knowledge about important aspects such as sexual and reproductive health. Therefore, it is essential to carry out health promotion activities with truthful information that allows this group to empower themselvesto make informed, safe, and responsible decisions, allowing them to protect themselves from factors that could expose them to risky situations. The objective of this research is to determine nursing interventions in the promotion of sexual and reproductive health in adolescents. A descriptive and documentary literature review was conducted; articles published between 2018 and 2024 were analyzed using reliable databases. The analysis of the selected studies identified that the usual sources of information preferred by this age group are parents and the content elaborated on the web, followed by teachers of the educational units and friends; however, the information is not always adequate, as a last resource they prefer health personnel, it is worth mentioning that the resolution of their concernsis more accurate when health workers provide the information since they are trained and have skills to communicate; nevertheless, access is still limited. It is attributed to the obstacles that impede the normal development of these activities, such as the lack of command of the language of rural communities, mobilization problems, economic limitations, and lack of political support. Therefore, frequent nursing intervention is necessary to strengthen the integration of the study population in the management, self-care, and maintenance of their health, thus contributing not only to their individual well-being but also to the development of healthier communities.